Development of a Web-Based Extracurricular Information System Using the Waterfall Model - Savio Nelinhos Dos Santos; Hanifah Permatasari; Eko Purwanto (Komunitas Dosen Indonesia, 2025)
Extracurricular activities are an important part of the holistic development of students which includes the formation of character, interests, talents, and social skills. However, many educational institutions still manage these activities manually through spreadsheets and printed documents, resulting in data duplication, information delays, and low transparency. This research aims to design and develop a web-based extracurricular information system to support the administration, monitoring, and evaluation of activities in an efficient and structured manner. The development of the system uses the Waterfall model chosen for its sequential and well-documented workflow, suitable for systems with predefined needs from the outset. The development stages include needs analysis, system design using UML, implementation with Laravel 9 and MySQL, as well as testing through the Black Box method and direct evaluation by the end user. The results of the Black Box test show that all system features are working according to specifications. Additionally, feedback from users shows a high level of satisfaction with the ease of use, navigation, and relevance of the features provided. This system successfully overcomes administrative challenges in managing extracurricular activities and is able to improve operational efficiency and user engagement. With the support of features such as automatic periodic assessments, PDF reports, notifications to parents, as well as a multilingual interface, the system has the potential to be more widely adopted by educational institutions that have similar contexts.